Spolna disfunkcija pri slovenskih pacientih z multiplo sklerozo - Pirečnik Noč, Anita (Obzornik zdravstvene nege, 2020)
Introduction: Although sexual dysfunction in multiple sclerosis patients is frequent, there is no data for Slovenian population. The purpose of the present study was to examine the form and prevalence of sexual dysfunction, differences between males and females, and a potential link between patient characteristics and sexual dysfunction. Methods: A cross-sectional study was conducted on patients with MS who have had sexual relation within the last 6 months and who completed the MSISQ-19 (Multiple Sclerosis Intimacy and Sexuality Questionnaire). 386 patients were included in the study with an average age of 40.9 years, and a duration of illness of 10.2 years. Neurological dysfunction was assessed with the EDDS (Expanded disability status scale). For a comparison of numerical variables and categorical variables, the unpaired t-test and a hi-square test were used, respectively. The correlation between patient characteristics and the type of sexual dysfunction was assessed by using the Spearman coeficient. Results: The proportion of sexual dysfunction, defined as answer 4 or 5 to any question in the MSISQ-19, was 37 %. The proportions of primary, secondary and tertiary sexual dysfunction were 39.4 %, 39.9 % and 40.8 %, respectfully. There were no statistically significant differences between males and females. A statistically significant but highly weak linear correlation was demonstrated between patient characteristics (age, MS duration, EDSS, duration of partnership) and different forms of sexual dysfunction. Discussion and conclusion: Sexual dysfunction is present in 37 % of Slovenian MS patients. There are no statistically significant differences between men and women, which is also true for individual forms of sexual dysfunction including primary, secondary and tertiary sexual dysfunction.
Keywords: demielinizacija; demielinization; disability; motnje; multipla skleroza; multiple sclerosis; sexuality; spolnost